Proceedings of the Fourteenth ACM Conference on Electronic Commerce 2013
DOI: 10.1145/2492002.2482612
|View full text |Cite
|
Sign up to set email alerts
|

Revenue optimization in the generalized second-price auction

Abstract: We consider the optimization of revenue in advertising auctions based on the generalized second-price (GSP) paradigm, which has become a de facto standard. We examine several different GSP variants (including squashing and different types of reserve prices), and consider how to set their parameters optimally. One intriguing finding is that charging each advertiser the same per-click reserve price ("unweighted reserve prices") yields dramatically more revenue than the quality-weighted reserve prices that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Mechanism design for online advertising has been extensively studied in the literature. Many discussions have been centered around search advertising auctions, such as the generalized first-price auction (Edelman et al, 2007), the generalized second-price auction (Edelman et al, 2007;Lahaie and McAfee, 2011;Lahaie and Pennock, 2007;Varian, 2007), the Vickrey-Clarke-Groves (VCG) auction (Parkes, 2007;Varian, 2009;Varian and Harris, 2014) and the optimal auction (Feldman et al, 2010;Ostrovsky and Schwarz, 2011;Thompson and Leyton-Brown, 2013) which extends Myerson's optimal auction for a single indivisible good (Myerson, 1981). Most of these studies on advertising auctions examine the properties of an auction model with respect to incentive compatibility, expected revenue, individual rationality, and computational complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Mechanism design for online advertising has been extensively studied in the literature. Many discussions have been centered around search advertising auctions, such as the generalized first-price auction (Edelman et al, 2007), the generalized second-price auction (Edelman et al, 2007;Lahaie and McAfee, 2011;Lahaie and Pennock, 2007;Varian, 2007), the Vickrey-Clarke-Groves (VCG) auction (Parkes, 2007;Varian, 2009;Varian and Harris, 2014) and the optimal auction (Feldman et al, 2010;Ostrovsky and Schwarz, 2011;Thompson and Leyton-Brown, 2013) which extends Myerson's optimal auction for a single indivisible good (Myerson, 1981). Most of these studies on advertising auctions examine the properties of an auction model with respect to incentive compatibility, expected revenue, individual rationality, and computational complexity.…”
Section: Related Workmentioning
confidence: 99%
“…auction using the optimal reserve price. Thompson and Leyton-Brown (2013) also studied several different techniques for increasing the revenue, including via several different reserve prices, squashing, combinations of a reserve price and squashing, ect. Rather than using the reserve price simply as a minimum bid, Roberts et al (2016) presented the idea of incorporating the reserve price into ranking score and showed that this mechanism may increase the revenue compared to the squashing mechanism.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have also examined and improved auction mechanisms, including better CTR estimates [6,16], usage of reserve prices in ad auction [30,34], and optimization in multiplicative bidding [3]. Using a sample from a week's worth of data across all keywords on Bing, other work [4] showed how to optimize linear combinations of the stakeholder utilities, showing that these can be tackled through a GSP auction with a per-click reserve price.…”
Section: Related Workmentioning
confidence: 99%